1994
DOI: 10.1111/j.1432-1033.1994.tb18921.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning of a novel luteinizing‐hormone/ human‐chorionic‐gonadotropin‐receptor cDNA

Abstract: The biological action of luteinizing hormone/human chorionic gonadotropin (lutropidchoriogonadotropin) in the ovary is mediated by interaction with its specific receptor. Lutropinlchoriogonadotropin-receptor hnRNA is processed into multiple mRNAs. However, nucleotide sequences for many of the transcripts, including the major form (6.7 kb), have yet to be determined. In an attempt to identify a cDNA encoding the major transcript, we have isolated a 3.5-kb cDNA clone from a rat ovary cDNA library. The 3.5-kb cDN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Extension in the 3Ј direction is more likely considering that the 3Ј-untranslated region of our clone is extremely AT-rich and has a noncanonical poly(A) addition signal. The association of a short coding region with a relatively large mRNA, on the other hand, has already been reported for the small Maf proteins and for other genes (57)(58)(59). Alternatively the higher molecular mass bands could derive from cross-hybridization to related MAF oncogenes or be highly expressed splicing isoforms of the same hMAF gene.…”
Section: Resultsmentioning
confidence: 77%
“…Extension in the 3Ј direction is more likely considering that the 3Ј-untranslated region of our clone is extremely AT-rich and has a noncanonical poly(A) addition signal. The association of a short coding region with a relatively large mRNA, on the other hand, has already been reported for the small Maf proteins and for other genes (57)(58)(59). Alternatively the higher molecular mass bands could derive from cross-hybridization to related MAF oncogenes or be highly expressed splicing isoforms of the same hMAF gene.…”
Section: Resultsmentioning
confidence: 77%
“…RM/l is a well characterized antibody that has been used successfully to demonstrate Gas in a variety of animal and human tissues (Morris et al, 1990;Europe-Finner et al, 1993). Strong functional evidence for an active Gas pathway is given by the finding that two unrelated agonists, hCG and PGE2, the receptors of which belong to the G protein-linked family (Hipkin et al, 1993;Bastien et al, 1994;Lu and Menon, 1994;Regan et al, 1994), provoke a large and rapid increase in cAMP production by granulosa cells. Strong functional evidence for an active Gas pathway is given by the finding that two unrelated agonists, hCG and PGE2, the receptors of which belong to the G protein-linked family (Hipkin et al, 1993;Bastien et al, 1994;Lu and Menon, 1994;Regan et al, 1994), provoke a large and rapid increase in cAMP production by granulosa cells.…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of this paper was to study G protein expression in human granulosa cells, and to investigate the functional involvement in receptor activation of G proteins by measuring second messenger formation in response to agonists that oper¬ ate through G protein-linked receptors (Kimura et al, 1992;Lu and Menon, 1994). Human chorionic gonadotrophin was used to stimulate adenylyl cyclase (McFarland et al, 1989;Cooke et al, 1989), and oxytocin was used to activate PLC (Schrey et al, 1987;Phaneuf et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Four rat LH/hCG receptor transcripts of 6.7, 4.4, 2.6, and 1.8 kb in length have been identified in ovarian tissue [10]. Studies conducted in our laboratory have shown that the 6.7-kb transcript is the most abundant form found in rat ovary and is an extension of the 4.4-kb transcript in the 3Ј untranslated region [46]. In fact, all four transcripts appear to be derived from the same cDNA.…”
Section: Lh/hcg Receptor Genomic Organization and Mrna Transcriptsmentioning
confidence: 95%